BODY AND CITY: A NEW ANATOMY (Fiep Bulletin - online, 2017)
This article discusses the relationship between the body and the urban transformations from the analysis on thesociological questions of the body. Through the evolution of public health, accessibility and new means of mobility. It also requiresdebate on the new possibilities of this body, such as the cyborg body.
Keywords: body; city; cyborg